The effectiveness of principal academic supervision on Indonesian language learning in remote schools: A study at UPT SD Negeri 6 Batu - Herawati R; Muhammad Hanafi; Yusmah Yusmah (Universitas Muhammadiyah Enrekang, 2025)
This study investigates the effectiveness of the principal’s academic supervision on Indonesian language learning in a remote elementary school setting, focusing on UPT SD Negeri 6 Batu, Sidenreng Rappang Regency. Academic supervision is a key component in improving instructional quality, particularly in remote schools that face limited resources, uneven teacher competencies, and minimal professional development opportunities. Using a qualitative descriptive approach, this research examines how supervisory planning, implementation, and follow-up actions contribute to teacher professional competence, instructional quality, and work motivation. Data were collected through in-depth interviews, classroom observations, documentation analysis, and teacher questionnaires. The findings reveal that the principal’s supervision is systematically planned through scheduled supervision programs, clear instructional criteria, and structured performance monitoring. Implementation involves directive, nondirective, and collaborative approaches, including classroom observations, professional dialogues, and a peer-discussion model known as “safari pembelajaran.” The study shows that effective supervision enhances teachers’ readiness in instructional planning, strengthens their pedagogical strategies, and improves classroom management during Indonesian language lessons. Furthermore, supervision contributes to increased teacher motivation, greater responsibility, and improved discipline in carrying out instructional duties. The study concludes that academic supervision plays a significant role in improving the quality of Indonesian language learning in remote schools, and it recommends more sustained, reflective, and context-responsive supervisory practices to strengthen instructional outcomes.